The Czech middle class tourist's vision of a „real tourist“ and their efforts to disseminate the principles of tourism in the Czech lands in the second half of the nineteenth century (Theatrum historiae, 2013)
The second half of the ninghteenth century is a period when a modern turism was born as one of the results of an industrial society. Considering a growing importance of leisure in the middle class, the tourism became an alternative, how to spend it. Since that time leisure has been accessible not only for noblemen but for members of the middle class as well. The purpose of this article is to describe a Czech middle class touristic (hiking) community in the second half of the ninghteenth century. The research is based on the revue of The Czech Tourist Club, called The Revue of Tourists. The findings of the article are expected to reveal a charachter of relations among midle class active tourists and their opinions on disseminating of touristic principles in the society.